Elevated Osteoprotegerin Predicts Declining Renal Function in Elderly Women: A 10-Year Prospective Cohort Study - Lewis, J.; Lim, W.; Zhu, K.; Wong, G.; Dhaliwal, Satvinder; Lim, E.; Ueland, T.; Bollerslev, J.; Prince, R. (American Society of Neuroradiology, 2014)
Background: Elevated osteoprotegerin (OPG) levels are inversely correlated with creatinine clearance and end-stage renal disease in patients with diabetes, however its role in predicting decline in renal function and progression to a more advanced stage disease in the elderly general population is unknown. Methods: This was a prospective cohort study of 1,157 elderly women with serum OPG measured in 1998 and renal function estimated using serum creatinine and cystatin C-based estimated glomerular filtration rate (eGFR) at 5-yearly intervals. The primary objective of the study was to determine the relationship of circulating OPG levels with 5- and 10-year renal decline. Results: At baseline, participants with elevated OPG above the median (≥2.2 ng/ml) had a 5.0% lower CKD-EPI-creatinine and cystatin C eGFR compared to participants with lower OPG levels. In multivariable-adjusted linear regression models, elevated OPG levels at baseline were associated with greater 5- and 10-year decline in CKD-EPI-creatinine and cystatin C eGFR (-0.105, p = 0.002 and -0.104, p = 0.010, respectively). Elevated OPG at baseline was associated with increased 5- and 10-year risk of rapid renal decline (OR 2.13, 95% CI 1.33-3.43, p = 0.002 and OR 4.10, 95% CI 1.49-11.27, p = 0.006, respectively) and renal disease hospitalizations or deaths (HR 1.99, 95% CI 1.31-3.03, p = 0.001) after adjusting for known risk factors. Conclusion: Elevated OPG levels are associated with long-term renal dysfunction and may be provide a useful biomarker to predict the trajectory of renal decline in older women.